Evaluation of text input mechanisms for wearable computers - Thomas, B.; Tyerman, S.; Grimmer, K. (Virtual reality : the journal of the Virtual Reality Society, 1998)
This paper reports on an experiment investigating the functionality and usability of novel input devices on a wearable computer for text entry tasks. Over a 3-week period, 12 subjects used three different input devices to create and save short textual messages. The virtual keyboard, forearm keyboard, and Kordic keypad input devices were assessed for their efficiency and usability in simple text-entry tasks. Results collected included the textual data created by the subjects, the duration of activities, the survey data and observations made by supervisors. The results indicated that the forearm keyboard is the best performer for accurate and efficient text entry while other devices may benefit from more work on designing specialist graphical user interfaces (GUIs) for the wearable computer.